Differential lower airway dendritic cell patterns may reveal distinct endotypes of RSV bronchiolitis. Issue 7 (16th August 2016) - Kerrin, Aoife; Fitch, Paul; Errington, Claire; Kerr, Dennis; Waxman, Liz; Riding, Kay; McCormack, Jon; Mehendele, Felicity; McSorley, Henry; MacKenzie, Karen; Wronski, Sabine; Braun, Armin; et al.
Abstract : Rationale: The pathogenesis of respiratory syncytial virus (RSV) bronchiolitis in infants remains poorly understood. Mouse models implicate pulmonary T cells in the development of RSV disease. T cell responses are initiated by dendritic cells (DCs), which accumulate in lungs of RSV-infected mice. In infants with RSV bronchiolitis, previous reports have shown that DCs are mobilised to the nasal mucosa, but data on lower airway DC responses are lacking. Objective: To determine the presence and phenotype of DCs and associated immune cells in bronchoalveolar lavage (BAL) and peripheral blood samples from infants with RSV bronchiolitis. Methods: Infants intubated and ventilated due to severe RSV bronchiolitis or for planned surgery (controls with healthy lungs) underwent non-bronchoscopic BAL. Immune cells in BAL and blood samples were characterised by flow cytometry and cytokines measured by Human V-Plex Pro-inflammatory Panel 1 MSD kit. Measurements and main results: In RSV cases, BAL conventional DCs (cDCs), NK T cells, NK cells and pro-inflammatory cytokines accumulated, plasmacytoid DCs (pDCs) and T cells were present, and blood cDCs increased activation marker expression. When stratifying RSV cases by risk group, preterm and older (≥4 months) infants had fewer BAL pDCs than term born and younger (<4 months) infants, respectively. Conclusions: cDCs accumulate in the lower airways during RSV bronchiolitis, are activated systemically and may, through activation of T cells, NK T cells and NK cells, contribute to RSV-induced inflammation and disease. In addition, the small population of airway pDCs in preterm and older infants may reveal a distinct endotype of RSV bronchiolitis with weak antiviral pDC responses.